Sorts of Cargos on Architectural Buildings and their Reconstructions - Mazin Taleb Jared, Abdulsamed adnan lafta, Zainab lateef khudhair (International Journal of Advanced Science and Technology, 2019)
The objective of this paper is to study the types of loads on architectural buildings and conduct experimental studies of the strength of brick structures reinforced with carbon fiber canvases on the effect of static and dynamic loads.